2019
DOI: 10.14393/bj-v35n5a2019-36226
|View full text |Cite
|
Sign up to set email alerts
|

Psychological suffering of patients transplanted with hematopoietic stem cells

Abstract: Hematopoietic stem cell transplantation (HSCT) affects serious risks for the patient, including death. For this reason, it is considered a treatment that can cure or can present morbidities and lead to death. In this context, patients experience the first psychological conflicts before this transplant. To describe the psychological suffering developed by patients transplanted with hematopoietic stem cells from a referral service in the state of Rio Grande do Norte. This is a cross-sectional study with a quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
0
10
0
7
Order By: Relevance
“…Therefore, it is valid to emphasize the need for psychological support ( 21 , 25 ) . A study of 272 patients showed that HCT, whether autologous or allogeneic, is a treatment that triggers psychological disorders, such as anxiety and depression, in any of its phases, from pre to post-procedure ( 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is valid to emphasize the need for psychological support ( 21 , 25 ) . A study of 272 patients showed that HCT, whether autologous or allogeneic, is a treatment that triggers psychological disorders, such as anxiety and depression, in any of its phases, from pre to post-procedure ( 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this, it is important to mention that, in order to know when the patient should undergo apheresis, a test called CD34+ must be performed (this is an antigen found on the surface of a very early blood cell that is important in the formation of the bone marrow) this detects the birth of new stem cells (Molina, 2022;CD34 Test & Nicklaus Children's Hospital, n.d.) Therefore, according to the medical diagnosis, in some patients the process of cryopreservation or preservation occurs and in others not, this process consists of storing the collected stem cells in bags that are gradually frozen in liquid nitrogen until they reach a temperature of -196°C according to (de León, n.d.) until the patient returns to the conditioning phase. Regarding this phase, he mentions (Azevedo et al, 2019;n.d. ) which is the most difficult stage that the patient will go through since it will suffer an impact on psychosocial well-being related to the restrictions that this process has, one of the most important is that the patient is admitted under a protective isolation of long duration with the main purpose of protecting their vulnerability to contracting infections.…”
Section: Carolina García Castillo Et Al (2020)mentioning
confidence: 96%
“…The age ranged from 14 to 67 years, with a mean age of 42.07 years, and 51.16% were women. Among patients who underwent HSCT and presented psychological disorders, 27.91% had multiple myeloma (MM) transplantation as the main diagnosis, 58.14% received autologous transplantation, and the most cited psychological suffering in the records was anxiety (62.79%) (Azevedo et al, 2019).…”
Section: Carolina García Castillo Et Al (2020)mentioning
confidence: 99%
“…Durante as etapas que sucedem o procedimento, o paciente e seus familiares vivenciam momentos de ansiedade, angústia e incertezas, que podem causar estresse e interferir na sua recuperação e em seu cotidiano. A alta hospitalar influencia no imaginário dos sujeitos envolvidos, de forma especial com o paciente, uma vez que será preciso readaptar-se a sua rotina diária, além da possibilidade de recidiva da doença e o aparecimento de complicações relativas à toxicidade dos medicamentos ou até mesmo à DECH (Costanzo, et al, 2013;Azevedo, et al, 2019).…”
Section: As Tecnologias Em Saúde No Contexto Do Transplante De Célula...unclassified
“…A complexidade que permeia o TCTH evidencia a importância de uma equipe multiprofissional especializada, capacitada e que possua conhecimento dos vários tipos de tecnologias em saúde para subsidiar tal procedimento (Nascimento, et al, 2014;Azevedo, et al, 2019). Nesse contexto, a equipe necessita continuamente atuar de forma transdisciplinar, com centralidade no paciente e ancorada em conhecimentos técnico-científicos.…”
Section: Introductionunclassified